Blood Matters: A journey Along the Genetic Frontier - Masha Gessen (Granta, 2007)
In 2004 genetic testing revealed that Masha Gessen had a mutation that predisposed her to ovarian and breast cancer. This is a guide to this unfamiliar and unsettling territory, pointing the way towards the radical transformation genetic information is engineering in our sense of who we are and what we might become.